Indium Phosphide Membrane Nanophotonic Integrated Circuits on Silicon. Issue 3 (20th December 2019) - Jiao, Yuqing; van der Tol, Jos; Pogoretskii, Vadim; van Engelen, Jorn; Kashi, Amir Abbas; Reniers, Sander; Wang, Yi; Zhao, Xinran; Yao, Weiming; Liu, Tianran; Pagliano, Francesco; Fiore, Andrea; et al.
Abstract : Photonic integration in a micrometer‐thick indium phosphide (InP) membrane on silicon (IMOS) offers intrinsic and high‐performance optoelectronic functions together with high‐index‐contrast nanophotonic circuitries. Recently demonstrated devices have shown competitive performances, including high side‐mode‐suppression ratio (SMSR) lasers, ultrafast photodiodes, and significant improvement in critical dimensions. Applications of the IMOS devices and circuits in optical wireless, quantum photonics, and optical cross‐connects have proven their performances and high potential. Abstract : Indium phosphide (InP) membrane photonics on silicon (IMOS) combines the high‐density nanophotonic circuitries and the high‐efficiency direct‐bandgap optoelectronics in a single micrometer‐thick membrane layer. It enables strong light‐matter interaction in the membrane, leading to a range of performance enhancements. Integrating this InP membrane on electronics wafer will enable revolutionary cointegration and convergence of photonics and electronics.